2019
DOI: 10.3390/diagnostics9010019
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Special Issue on “Electromagnetic Technologies for Medical Diagnostics: Fundamental Issues, Clinical Applications and Perspectives”

Abstract: The application of microwave technologies in medical imaging and diagnostics is an emerging topic within the electromagnetic (EM) engineering community [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Microwave imaging (MWI) can potentially offer these advantages, and has thus emerged as a promising alternative for diagnosing cardiovascular diseases which could be used prior to MRI or CT scans [4]. Efforts to develop MWI systems for medical diagnostics go back almost forty years, with several review papers, book chapters, and special issues reporting recent developments [5][6][7]. Amongst a large body of research in medical microwave imaging, which cannot possibly be fully reviewed here, we note that various experimental systems have been developed for breast cancer detection [8][9][10][11][12][13][14], and more recently for stroke monitoring and detection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave imaging (MWI) can potentially offer these advantages, and has thus emerged as a promising alternative for diagnosing cardiovascular diseases which could be used prior to MRI or CT scans [4]. Efforts to develop MWI systems for medical diagnostics go back almost forty years, with several review papers, book chapters, and special issues reporting recent developments [5][6][7]. Amongst a large body of research in medical microwave imaging, which cannot possibly be fully reviewed here, we note that various experimental systems have been developed for breast cancer detection [8][9][10][11][12][13][14], and more recently for stroke monitoring and detection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Gains in image quality imparted through these modifications to the imaging algorithm are preserved across different frequency bandwidths and boundary condi- Methods of utilizing MWI for biomedical applications have been investigated for almost half a century [71,72]. Some recent representative research can be found in [73]. MWI algorithms can be split into those producing qualitative images, where the reconstructed value at each pixel is a relative quantity, and those producing quantitative reconstructions of a physical property, typically the complex-valued permittivity.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave imaging (MWI) for medical applications is gaining increasing interest from various research groups worldwide, as it is safe, non-invasive, and has potential to lead to low-cost and portable devices [1]. MWI methods reconstruct the distribution of tissues with different electric properties by solving an electromagnetic inverse scattering problem [2].…”
Section: Introductionmentioning
confidence: 99%